The Indonesian Throughflow and its association with the Atlantic Ocean circulation - Santis Junior, Wlademir Jose de (2017)
Experiments with a coupled atmosphere-ocean-sea ice model using idealized topographies were run to investigate aspects of the role that the lateral ocean constraints play in the climate. The experiments consider an idealized planet covered with a constant deep ocean, where one-grid-wide land barriers were gradually added. The series of experiments allowed the investigation of many aspects of the coupled system equilibrium and variability, ending with an evaluation of the effects of the Indonesian Throughflow. Rather than to investigate the throughflow\'s impacts in modern climate, which has been largely explored in numerical experiments in the past decades, the throughflow is investigated in an alternative climate, argued as a possible scenario during ice-age periods. It was found that the change in the hemispheric water source of the throughflow affects many aspects of its impact as it is known for modern climate. In summary, the throughflow acts within the inter-basin seesaw in the sense to restore the previous phase of the inter-basin seesaw.